Analisis dan Implementasi Algoritma Asimetris Dual Modulus RSA (DM-RSA) pada Aplikasi Chat - Aminudin; Ilyas Nuryasin (Ikatan Ahli Informatika Indonesia (IAII), 2021)
The RSA algorithm is one of the cryptographic algorithms with an asymmetric model where the algorithm has two keys, namely the public key and the private key. However, as time goes on, these algorithms are increasingly exposed to security holes and make this algorithm vulnerable to being hacked by people who do not have authority. The vulnerability stems from the algorithm's public keys (e and n). The strength of the RSA algorithm is based on the difficulty of factoring two prime numbers that are generated during the key generation process, if these values ​​can be known using certain methods, the public key and private key values ​​will be found. Therefore, there are many studies that improvise the RSA algorithm, one of which is the Dual Modulus RSA (DM-RSA) algorithm. The algorithm uses four prime numbers which produce 2 modulus and 4 keys (2 public keys and 2 private keys). From the results of the Kraitchik factorization test, it was found that the DM-RSA algorithm was proven to be more resistant up to 2 times or even more than the standard RSA algorithm. This is evidenced by the fact that the value of n is 24 bits, the RSA algorithm can last up to 63204 ms (1 minute 22 seconds) while the Dual Modulus RSA algorithm lasts up to 248494123 ms (142 minutes 47 seconds).